Technical Perspective: New Developments in Graph Partitioning. - Tardos, Éva (Communications of the ACM, 2008)
The article discusses developments in graph partitioning, presenting a review of another article in the issue that surveys developments in approximation algorithms from 1998 to 2008. The author states that graph partitioning played a role in research about algorithms and algorithmic techniques. Topics include packetrouting in distributed networks, parallel computing architectures and algorithms, and finding an optimal balanced partition. Also discussed are algorithms based on semidefinite programming.